The Proviral Reservoirs of Human Immunodeficiency Virus (HIV) Infection - Andrey I. Murzin; Kirill A. Elfimov; Natalia M. Gashnikova (Pathogens)
Human Immunodeficiency Virus (HIV) proviral reservoirs are cells that harbor integrated HIV proviral DNA within their nuclear genomes. These cells form a heterogeneous group, represented by peripheral blood mononuclear cells (PBMCs), tissue-resident lymphoid and monocytic cells, and glial cells of the central nervous system. The importance of studying the properties of proviral reservoirs is connected with the inaccessibility of integrated HIV proviral DNA for modern anti-retroviral therapies (ARTs) that block virus reproduction. If treatment is not effective enough or is interrupted, the proviral reservoir can reactivate. Early initiation of ART improves the prognosis of the course of HIV infection, which is explained by the reduction in the proviral reservoir pool observed in the early stages of the disease. Different HIV subtypes present differences in the number of latent reservoirs, as determined by structural and functional differences. Unique signatures of patients with HIV, such as elite controllers, have control over viral replication and can be said to have achieved a functional cure for HIV infection. Uncovering the causes of this phenomenon will bring humanity closer to curing HIV infection, potential approaches to which include stem cell transplantation, clustered regularly interspaced short palindromic repeats (CRISPR)/cas9, “Shock and kill”, “Block and lock”, and the application of broad-spectrum neutralizing antibodies (bNAbs).